2003
DOI: 10.1016/s0008-6363(03)00261-x
|View full text |Cite
|
Sign up to set email alerts
|

Trapidil protects ischemic hearts from reperfusion injury by stimulating PKAII activity

Abstract: The data demonstrate cardioprotective actions of trapidil in I/R and show a PKAII-dependent cAMP sensitizing effect of the compound. They also indicate PKA-dependent PLB phosphorylation as a target, suggesting an improved Ca(2+) uptake by the sarcoplasmic reticulum. This action might be involved in the cardioprotective effects of trapidil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…To gain insight into the potential mechanisms responsible for insulininduced modification of ISO activated b-adrenergic action, we further evaluated SERCA2a activity, PLB phosphorylation and PKA activation, as possible targets for insulin interaction with b-AR initiated signaling cascade. Our study showed that there was significant reduction in PKAdependent PLB phosphorylation, SERCA2a expression and subsequent SERCA2a activity in I/R myocardium, which were in accordance with the reports from Temsah et al [15] and Sichelschmidt et al [36]. Moreover, ISO induced additional decrease in SERCA2a expression and activity, although PLB phosphorylation was increased compared with the untreated I/R hearts.…”
Section: Discussionsupporting
confidence: 93%
“…To gain insight into the potential mechanisms responsible for insulininduced modification of ISO activated b-adrenergic action, we further evaluated SERCA2a activity, PLB phosphorylation and PKA activation, as possible targets for insulin interaction with b-AR initiated signaling cascade. Our study showed that there was significant reduction in PKAdependent PLB phosphorylation, SERCA2a expression and subsequent SERCA2a activity in I/R myocardium, which were in accordance with the reports from Temsah et al [15] and Sichelschmidt et al [36]. Moreover, ISO induced additional decrease in SERCA2a expression and activity, although PLB phosphorylation was increased compared with the untreated I/R hearts.…”
Section: Discussionsupporting
confidence: 93%
“…Possible mechanisms include (i) calpain inhibition and reduced cell death [41] (ii) increased HSP27 activation [42] (iii) phospholamban phosphorylation, causing increased SR Ca 2+ uptake and a reduction in cytosolic Ca 2+ [43] (iv) inhibition of the small GTPase RhoA and its downstream Rho-kinase, known to enhance cardiac damage in acute ischaemia [6,[44][45][46][47]. It is also possible that, both in the case of β1-and β2-AR preconditioning, PKA activation leads to switching their coupling from Gs to Gi and activation of ERKp42/p44, as has been demonstrated by Martin and coworkers [37].…”
Section: What Happens Downstream Of the β-Ar?mentioning
confidence: 99%
“…The importance of PKA in increasing cardiac contractile activity, post β-AR stimulation, is emphasized by the discovery that cardiospecific overexpression of the β 2 -AR transgene increases ventricular function in vivo , and modulates cardiomyocyte gene expression by phosphorylating its cAMP-response element binding protein transcription factor [19,20]. Phosphorylation of PLB by PKA has also been demonstrated to increase Ca 2+ affinity of the SR Ca 2+ pump and calcium current I Ca -triggered Ca 2+ -induced Ca 2+ -release from the SR Ca 2+ stores [21,22,23]. Since these alterations in SR PLB function were found to be independent of those in SR Ca 2+ pump ATPase in heart failure (HF), PKA-PLB interaction is considered to be a target for drug development for the treatment of HF [24].…”
Section: Protein Kinase Amentioning
confidence: 99%
“…However, inhibition of PKA has also been demonstrated to exert detrimental effects pertaining to cardiac function, specifically concerning protection from I/R injury [23,65,66,67]. In adult rats, PKA inhibitors were shown to prevent the growth hormone releasing hormone (GHRH) induced protective benefits on cardiac performance in I/R injury [65].…”
Section: Protein Kinase Amentioning
confidence: 99%